Economic analysis for a brewery wastewater - Camargo, José Rui; Deo, Vicente Fachina (Revista Ciências Exatas, 2008)
This paper focuses upon mathematical modeling the methane yield from the anaerobic digesting process of a brewery wastewater, whose variables are shown in a parameter diagram format for conveniently separating them in four distinct groups. Basing on mass balance and empirical relations, one builds a numerical simulating system comprising off our differential equations, the anaerobic digesting of organic matter, biogas yielding, methane molar fraction and methane exergy flow. Two dimensionless performance metrics, the organic matter reduction factor, and the methane to biomass yield factor, the former already known and the latter defined in this work, are used to build a phased space plotting for process monitoring purposes. An exergy flow and a specific exergy flow equations are derived based on those dimensionless performance metrics, and then they are plotted together by a numerical simulation. Finally, an economic analysis is performed by using rough estimatives to aid on decision-making processes for harnessing such an energy source for practical usage.